Reduction of multidimensional poverty and strength of social inclusion through a municipal program. The case of the impact assessment of the program «Un Solo San Pedro» - Portales, Luis (Iberoamerican Journal of Development Studies, 2010)
Poverty is the Objective of Sustainable Development number 1, encouraging local governments to create programs aimed at its reduction. However, poverty worldwide and in Mexico has been reduced marginally, making impact assessments more critical. In this article, it is presented the results of the evaluation of the «Un Solo San Pedro» program, aimed at reducing multidimensional poverty and strengthening social inclusion in fourteen neighborhoods of San Pedro Garza García, a Mexican municipality. The results show the impact that the program had in the reduction of multidimensional poverty and the improvement in social inclusion indicators, as well as the difficulty that represents the change of cultural patterns linked to this problem. The article contributes to the generation of knowledge about the value of these evaluations in the understanding of poverty and the impact that programs have on their eradication.
Keywords: pobreza multidimensional; inclusión social; evaluación de impacto; programa de combate a la pobreza; municipio